In Vitro Alkaline pH Resistance of Enterococcus faecalis - Weckwerth, Paulo Henrique; Zapata, Ronald Ordinola; Vivan, Rodrigo Ricci; Tanomaru Filho, Mario; Maliza, Amanda Garcia Alves; Duarte, Marco Antonio Hungaro (Fundação Odontológica de Ribeirão Preto, 2013)
Enterococcus faecalis is a bacterial species often found in root canals with failed endodontic treatment. Alkaline pastes are widely used in Endodontics because of their biocompatibility and antimicrobial activity, but this microorganism can resist alkalinity. The purpose of this study was to evaluate in vitro the alkaline pH resistance of E. faecalis for different periods up to 14 days. Samples were obtained from the oral cavity of 150 patients from the Endodontic clinic. The pH of the experimental tubes (n=84) was first adjusted with 6M NaOH to pH values of 9.5, 10.5, 11.5 and 12.5 (21 tubes per pH). Twenty clinical isolates and the ATCC 29212 strain were tested. The 5 positive controls and experimental tubes of each pH were inoculated with 10 µL of bacterial suspension and incubated at 36 °C for 24, 48 and 72 h, 7 and 14 days. For each period, the turbidity of the medium was visually compared with a 0.5 McFarland standard. The presence of the microorganism was confirmed by seeding on M-Enterococcus agar. Four tubes containing BHI broth adjusted to the tested pHs were incubated for 14 days to verify if pH changes occurred. The pH of inoculated BHI broth was also measured on day 14 to determine if the microorganism acidified the medium. The growth of all E. faecalis strains occurred at pH 9.5 to 11.5 in all periods. Although turbidity was not observed at pH 12.5, there was growth of 13 and 2 strains at 24 and 48 h, respectively, on M-Enterococcus agar. No tube showed growth at pH 12.5 after 72 h. It was concluded that E. faecalis can survive in highly alkaline pH, and some clinical isolates require 72 h at pH 12.5 to be killed.

Enterococcus faecalis é uma espécie bacteriana frequentemente encontrada em canais radiculares com insucesso do tratamento endodôntico. Pastes alcalinas são amplamente utilizada em Endodontia por causa de sua biocompatibilidade e atividade antimicrobiana, porém esse microrganismo pode ser resistente a alcalinidade. Este estudo avaliou in vitro a resistência do E. faecalis ao pH alcalino por diferentes períodos até 14 dias. Amostras foram obtidas da cavidade oral de 150 pacientes da Clínica de Endodontia. O pH dos tubes experimentais (n=84) foram inicialmente ajustados com NaOH 6M a valores de pH 9.5, 10.5, 11.5 e 12.5 (21 tubes per pH). Vinte isolados clínicos e a cepa ATCC 29212 foram testados. Os 5 controles positivos e os tubos experimentais de cada pH foram inoculados com 10 µL de suspensão bacteriana e incubados a 36 °C por 24, 48 e 72 h, 7 e 14 dias. Para cada período, turvação do meio foi compara visualmente com padrão 0.5 da escala de McFarland. A presença de microorganism foi confirmada por semeadura no meio ágar M-Enterococcus. Quatro tubos contendo caldo BHI ajustado aos pHs testados foram incubados por 14 dias para verificar a ocorrência de alterações de pH. O pH do caldo BHI inoculado também foi medido no 14° dia para determinar se o microrganismo acidificou o meio. O crescimento de todas as cepas de E. faecalis ocorreu com pH entre 9.5 e 11.5 em todos os períodos. Embora não tenha sido observada turvação do meio no pH 12.5, houve crescimento de 13 e 2 cepas às 24 e 48 h, respectivamente, no meio ágar M-Enterococcus. Nenhum tube apresentou crescimento bacteriano no pH 12.5 após 72 h. Concluiu-se que o E. faecalis pode sobreviver em pH altamente alcalino, que alguns isolados clínicos requerem 72 h em pH 12.5 para serem eliminados.
Keywords: Enterococcus faecalis; alkaline pH; microbial resistance